Hubungan Karakteristik Ibu dengan Kejadian Abortus Di Bagian Obsestri – Ginekologi RSUD Labuang Baji Makassar Selama Periode Januari 2021 – Desember 2022 - Azzahra, Sy. Fatimah; Amiruddin, Tedy; Murnita, Ika Azdah (Fakultas Kedokteran Universitas Bosowa, 2025)
Abortion is a threat or process of discharge of conception before the fetus can live outside the mother's womb with gestational age less than 20 weeks or fetal weight less than 500 grams. There are several risk factors associated with the occurrence of abortion. The purpose of the study was to determine the relationship between the characteristics of abortion patients based on (1) parity history (2) abortion history (3) pregnancy distance (4) occupation (5) history of anemia. The population of this study were pregnant women who experienced abortion with a total sample of 100 samples, of which there were 50 case populations and 50 control populations of pregnant women who were treated at the Obstetrics and Gynecology Department of Labuang Baji Hospital Makassar during the period January 2021 to December 2022. This study used observational and analytical qualitative methods with a case control research design using secondary data in the form of medical records of abortion patients hospitalized in the Obstetrics and Gynecology Department of Labuang Baji Hospital Makassar during the Period January 2021 to December 2022. Data analysis includes univariate and bivariate data using the chi-square test using SPSS software. The results of this study showed that groups of mothers with a history of parity were at risk (48.0%) and not at risk (52.0%) with a p-value of 0.317, a history of abortion was at risk (51.0%) and not at risk (49.0%) with a p-value of 0.689, pregnancy distance at risk (18.0%) and not at risk (82.0%) with p-value 0.014, occupation at risk (56.0%) and not at risk (44.0%) with p-value 0.314, and history of anemia at risk (28.0%) and not at risk (72.0%) with p-value 0.001. The conclusion of the study found that there was an association between pregnancy spacing and history of anemia.